Protocols for multi-step thermoplastic processing of metallic glasses. (15th July 2015) - Bordeenithikasem, Punnathat; Sohn, Sungwoo; Liu, Ze; Schroers, Jan
Abstract : Temperature profiles of multi-step thermoplastic forming of bulk metallic glasses were simulated by isothermal annealing at multiple temperatures and sequences. For a single annealing temperature, the time to crystallize is additive. When the sample is first annealed at a higher temperature and quenched to a lower temperature, time till crystallization is gained, and vice versa. These findings can be explained by the temperature dependence of nucleation and growth rates, which suggests the maximum nucleation temperature is below thermoplastic forming temperatures.